Pragmatic probe: preference and satisfaction with built environment - Mohamed Salim, Ferwati (Penerbit UTM Press, 2015)
Enhancing the quality of urban life is considered by social scientists. It has instigated a growing attention in findings from surveys aiming to measure the inhabitant image in particular places. This paper investigates preference and satisfaction that utilizes a model from both a conceptual and empirical perspective. It mainly explores the image of certain social-spatial factors enhanced in the degree of preference and satisfaction with neighborhood and housing types on both scales, as an overall and as details of urban elements and house features. It first presents a brief overview of literature and the methodology and then reviews findings covering 162 respondents living in two cities that represent four different neighborhood patterns, social-spatial characters, and housing types. The four neighborhoods are: traditional settlements, attached houses, tower apartments and single family houses. The major findings reveal that satisfaction within a given neighborhood does not necessarily associate with place attachment and similarly, despite realization of lacking certain social-spatial qualities in the neighborhood, people may feel attached to the place because of certain attributes. However, there is on one hand a positive relationship between satisfaction and feelings of a neighborhood as home, and on the other hand, differences in preference and satisfaction of house types, urban elements and house features.